Macula densa cell angiogenic mechanisms and their therapeutic potential in kidney disease - Gyarmati, Georgina; Desposito, Dorinne; Riquier-Brison, Anne; Becerra Calderon, Alejandra; Trogen, Greta; Izuhara, Audrey; Yamashita, Michifumi; Peti-Peterdi, János (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe neuronally differentiated key sensory and regulatory cells of the macula densa (MD) were recently identified to control resident progenitor cells and endogenous kidney tissue remodeling and regeneration. Among the many MD-derived secreted angiogenic, growth, and extracellular matrix remodeling factors, cell communication network 1 (CCN1) is a known positive modulator of angiogenesis. This study aimed to validate and characterize the angiogenic potential and mechanisms of MD-derived biologicals including CCN1 in control healthy and disease conditions.MethodsThe angiogenic effects of secreted MD cell factors including CCN1 on glomerular endothelial cells (GEnC) were studied in vivo using Cdh5-Confetti mice with endothelium-specific expression of multicolor genetic reporters for genetic cell fate tracking, and in vitro using cultured GEnCs in angiogenesis, cell proliferation and migration assays. The effects of treatment with conditioned MD cell culture media (rich in CCN1) were tested in NZM.2328 BAFF transgenic lupus mice using intravital multiphoton microscopy, histology, and classic kidney function phenotyping.ResultsHigh CCN1 expression in MD cells was confirmed in the mouse and human kidney with diminished levels in patients with lupus nephritis. GEnC angiogenesis assays confirmed the strong angiogenic potential of CCN1 and the mechanistic role of integrins β3 and β5, VEGFR2 and Akt signaling in this process. Treatment of NZM.2328 BAFF transgenic lupus mice with MD factors vs control improved GEnC function, halted the progression of albuminuria, and reduced immune cell homing. The implantation of cultured MDgeo cells but not control M1 cells under the renal capsule of Cdh5-Confetti mice induced the growth of new blood vessels radially towards the MD cell epicenter that were formed by clonal expansion of host endothelial cells.DiscussionThe present study confirmed the strong angiogenic effect of MD-derived factors including CCN1 that may be targeted in future biologicals, biofabricated tissue, or cell-based therapeutic developments for kidney diseases.